Dysfluencies in Nopnals Under D.A.F:1 - Nataraja NP; Ramesh MV; Raj Kumar Pandita (Journal of All India Institute of Speech and Hearing, 1970)
Lee  (1950), showed  that experimentally produced delay in air-conducted auditory feedback of speech causes widespread speech disruption. Primarily, delayed auditory feedback (DAF) produces a slower rate of speech, dysfluencies and articulatory errors (Lee, 1950, 1951; Black 1951; Fairbanks and Guttman,1951). Lee (1950, 1951) has given the term 'Artificial Stutterer' to a person speaking under  delayed auditory feedback. He  also says that subjects  under DAF might provide insights into the nature and etiology of stuttering. A hypo- theses given by Webster and Lubker (1968), was that a disturbance in auditory feedback might be responsible for stuttering. There  was an increase in the intensity, fundamental frequency  and  duration  of  speech  when  normals  were asked to speak with delayed auditory feedback, (Black  1950). The findings were similar to that of a normal under bilateral application of masking noise.